Edukasi Dan Pelatihan Budidaya Toga Di Pekarangan Rumah Warga Di Desa Pakuli - formakip formakip (Jurnal Pengabdian Masyarakat Akademisi, 2023)
Based on the results of our observations, there are problems that are of concern in Pakuli Village. One of the problems is that there are still many yards of residents' houses that are empty and not used as a place to plant family medicinal plants or